Penerapan Model Problem Based Learning (Pembelajaran Berdasarkan Masalah) dalam Meningkatkan Hasil Belajar PKN Pada Siswa Kelas V SD GMIM Picuan - Yulmi Hesti Mottoh (Peneliti.net, 2021)
The main problem in learning PKN in elementary schools is the use of learning models that only provide the ability to memorize, not to think critically and creatively. Teachers teach more to pursue targets that are oriented towards final exam scores. In addition, in using the learning model is still conventional, so students are less actively involved in the learning process. How is the Implementation of Problem Based Learning Model in Improving Civics Learning Outcomes? The purpose of this study was to obtain an overview of the application of problem-based learning models in improving Civics learning outcomes. This type of research is classroom action research. Using four stages of research. It is carried out in 2 cycles with the research subjects being fifth grade students of SD GMIM Picuan in the even semester of the 2020/2021 school year. Data were collected through observation, and tests. Analyzed using percentage analysis. The learning action is carried out in accordance with the prepared learning plan. With the acquisition of learning outcomes in the first cycle of test results obtained 74% seen student learning outcomes have not been successful, it is necessary to re-learn through cycle II. In the second cycle, the activities were carried out as in the first cycle with the results of the test of obtaining learning outcomes of 90.%. The conclusion of this research is the application of problem-based learning model can improve student learning outcomes, improve student learning skills and activities. It is expected that in carrying out learning the teacher should use a problem-based learning model because it can facilitate learning activities.